Correlation Between Size of Renal Cell Carcinoma and Its Grade, Stage, and Histological Subtype - Tabibi, Ali; Parvin, Mahmoud; Abdi, Hamidreza; Bashtar, Reza; Zamani, Nasim; Abadpour, Behrang (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to determine the correlation between histological subtype, size, grade, and stage of the kidney tumors and to investigate whether a correlation exists between the size of the kidney tumor and its behavior. Materials and Methods: Between 1996 and 2004, we had 212 patients with radical or partial nephrectomy due to a kidney tumor at Shaheed Labbafinejad Medical Center. Their pathologic blocks were re-evaluated with consideration of their tumor size and pathologic features. Results: Of 212 pathologic blocks, 17 (8%) were benign and 195 (92%) were malignant masses including 179 renal cell carcinoma (RCC) tumors. Malignant tumors were slightly greater compared with the benign ones (P = .10). There was no significant relation between the size of tumor and the histological subtype. Significant relations between the size of the kidney tumor and the nuclear grade (P = .007), clinical symptoms (P = .02), and extracapsular extension (P < .001) were observed. In smaller RCC tumors (< 4 cm), extracapsular extension (stages T3 and T4) was rare (1 in 29).Â  However, smaller RCC tumors were not significantly different from those larger than 4 cm regarding the nuclear grade, symptoms, and histological subtypes. Conclusions: Tumor size is not an independent predictor for the histological subtype of the tumors; however, larger malignant tumors may have higher grades, higher stages, and clinical symptoms.